2023
DOI: 10.1007/s11469-023-01072-4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Gender-Based Violence in Drug Addiction Treatment: a Systematic Mapping Review

Nuria Romo-Avilés,
Lorena Tarriño-Concejero,
Laura Pavón-Benítez
et al.

Abstract: Abstract“Intervention support and treatment” programs are most likely to have been designed for the substances consumed by men, and to cater for men’s needs, with little regard to the specific needs of women. Gender-based violence (GBV) has become a key area for addressing the treatment of drug addiction from a gender perspective. In this mapping review covering 32 articles, we examine the strategies used to address gender-based violence in drug addiction treatments that include women. The main topics of analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In the above study, it was found that Indigenous-based treatment services were the most likely to provide violence intervention, while solo practices, religiously affiliated healthcare centers and hospitals generally provided violence treatment options at a much lower rate ( 5 ). A recent review from Romo-Avilés and colleagues ( 20 ) documented under 20% of articles addressed gender based violence in studies offering addiction treatment, even though almost 60% of articles document the effects of violence seen among the populations served in treatment for drugs and alcohol. Almost two decades of research continually call out limited research that shows integrated treatment despite the clear link between violence and substance use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above study, it was found that Indigenous-based treatment services were the most likely to provide violence intervention, while solo practices, religiously affiliated healthcare centers and hospitals generally provided violence treatment options at a much lower rate ( 5 ). A recent review from Romo-Avilés and colleagues ( 20 ) documented under 20% of articles addressed gender based violence in studies offering addiction treatment, even though almost 60% of articles document the effects of violence seen among the populations served in treatment for drugs and alcohol. Almost two decades of research continually call out limited research that shows integrated treatment despite the clear link between violence and substance use.…”
Section: Introductionmentioning
confidence: 99%
“…This review considers intimate partner violence, sexual assault, stalking, child abuse, political and community violence, criminal violence, micro violence, and structural violence and oppression. A focus on treatment setting was chosen given the equivocal connection to relationships, violence, and offending, particularly for women ( 19 , 20 , 24 , 30 , 40 ).…”
Section: Introductionmentioning
confidence: 99%